Effect of slag content to cement grout on the compressive strength development in tropical weather environment - Lim, S. K.; Zakaria, F.; Hussin, M. W.; Muhamad, R. (2006)
Cement based grout is one of the economical and an effective material that is usually used for repairing structural cracks. This paper investigated the compressive strength development under different curing regimes of the cement-based grouts produced by various replacement levels of slag (GGBFS) compared with the 100 percent OPC based grout in tropical weather. This paper covered the investigation of the compressive strength of the ordinary Portland cement grout and the slag cement based fluid grouts with the replacement of GGBFS in range of 30 percent to 60 percent slag. All specimens were cured under three different curing conditions to investigate effect of curing regimes to the development of compressive strength. The investigation proved that the slag cement based grout could stand the tropical weather and provided the suitable strength for normal concrete structural repairing works. The test results showed that 50 percent slag replacement specimens provide optimum long-term compressive strength among others under water curing condition. The optimum slag replacement can enhance the strength of cement mixes in long-term under water curing regime. This has indicated a good sign for further investigation of other engineering properties to produce a more effective repairing material using slag as a partial cement replacement.